2017
DOI: 10.1016/j.jalz.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical stress increases brain amyloid β, tau, and α‐synuclein concentrations in wild‐type mice

Abstract: Dose-dependent and cumulative influence of repetitive mild traumatic brain injury-induced mechanical stress may trigger and/or accelerate neurodegeneration by pushing protein concentration over the disease threshold.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…It may be possible to monitor intra-seasonal sport related brain trauma through the evaluation of serum levels of the neurofilament-light chain, but this has not demonstrated good long-term prognostic accuracy to date [76]. Despite the association between tau and mechanical trauma [56], plasma levels of tau are not altered in accord with trauma frequency or severity during the course of an American football season [76]. The current and previous findings [72], suggest different forms of tau pathology provide a diverse set of markers to track CTE development and efficacy of tau-mediated treatments, especially in the pre-symptomatic stages of this disorder [7, 58, 72, 87].…”
Section: Discussionmentioning
confidence: 99%
“…It may be possible to monitor intra-seasonal sport related brain trauma through the evaluation of serum levels of the neurofilament-light chain, but this has not demonstrated good long-term prognostic accuracy to date [76]. Despite the association between tau and mechanical trauma [56], plasma levels of tau are not altered in accord with trauma frequency or severity during the course of an American football season [76]. The current and previous findings [72], suggest different forms of tau pathology provide a diverse set of markers to track CTE development and efficacy of tau-mediated treatments, especially in the pre-symptomatic stages of this disorder [7, 58, 72, 87].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study to investigate the link between TBI and neurodegenerative disorders, 5–6-week-old mice were exposed to multiple condition head impacts and the levels of several proteins were examined. The results showed that after repetitive TBI, there was an increase in brain amyloid β, tau, and α-syn in a dose-dependent manner [102]. α-Syn accumulation has also been detected in glial cells [3], predominantly in microglia compared to astrocytes [85].…”
Section: Exogenous and Environmental Factors Modulating Selective Regmentioning
confidence: 99%
“…Stress can increase APP and tau phosphorylation in AD progression (Caruso and others 2018). Repetitive mild TBI-induced mechanical stress increases brain levels of Aβ1-42 peptide, tau, and α-synuclein-mediated neurodegeneration in mice (Levy Nogueira and others 2018). Restraint stress in AD mouse models (Tg2576) showed increased Aβ (1-42), tau hyperphosphorylation, and cortical neuronal atrophy (Lee and others 2009).…”
Section: Influence Of Personal Traits On Tbi-mediated Ad Pathogenesismentioning
confidence: 99%